(untitled) - Bernard Hartley (New York, 1995)
This book is designed to follow "Departures", consolidating and building upon the oral skills. The material consists of 80 units, each clearly laid out on a separate page. The Teacher's Book contains the complete Student Book interleaved with detailed teaching notes. These give step-by-step instructions for using the material, ideas for additional activities, and comprehensive suggestions on how to present each new topic
Keywords: americanism,english language - textbooks for foreign speakers,english language - united states